2015
DOI: 10.1016/j.apmr.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Perceived Quality of Care Among Older Adults According to Activity Limitation Stages

Abstract: OBJECTIVE To examine whether patient satisfaction and perceived quality of medical care was related to stages of activity limitations among older adults. DESIGN Cross-sectional study. SETTING Medicare Current Beneficiary Survey (MCBS) for calendar years 2001-2011. PARTICIPANTS A population-based sample (n= 42,584) of persons 65 years of age and older living in the community. INTERVENTIONS Not applicable. MAIN OUTCOME MEASURE(S) MCBS questions were categorized under 5 patient satisfaction and perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Our conceptual model is consistent with our prior work 11 and represents the hypotheses examined in this study regarding how patient satisfaction with care coordination and quality and access to medical care may relate to activity limitation stage transitions, institutionalization, or death (Figure 1). The objectives of the present study were 1) to describe how socioeconomic characteristics and health-related conditions influence functional improvement or deterioration (activity limitation stage transitions), institutionalization, or death at 2 years; and 2) to assess whether patient satisfaction with care and access to medical care at baseline were related to activity limitation stage transitions, institutionalization, or death at 2 years.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our conceptual model is consistent with our prior work 11 and represents the hypotheses examined in this study regarding how patient satisfaction with care coordination and quality and access to medical care may relate to activity limitation stage transitions, institutionalization, or death (Figure 1). The objectives of the present study were 1) to describe how socioeconomic characteristics and health-related conditions influence functional improvement or deterioration (activity limitation stage transitions), institutionalization, or death at 2 years; and 2) to assess whether patient satisfaction with care and access to medical care at baseline were related to activity limitation stage transitions, institutionalization, or death at 2 years.…”
Section: Introductionsupporting
confidence: 81%
“…5-8 We found that ADL or instrumental activity of daily living (IADL) limitations, by defined stages, 9,10 were associated with dissatisfaction with care coordination and quality and access to medical care. 11 These findings add to a growing body of evidence suggesting that higher disability burden is associated with decreased satisfaction with medical care. To our knowledge, no published research to date has examined whether or not decreased satisfaction with medical care influences transitions across activity limitation stages (functional improvement or deterioration), institutionalization, or death among older adults.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…This report challenged governments, health systems, academic institutions, insurers, and communities to collaborate to enhance competence in geriatrics, to increase recruitment and retention of health professions focused on caring for older adults, and to explore new models of care. Although progress has been made, gaps remain between the care senior citizens seek and what they receive [5,6]. These problems reflect continued shortfalls in the availability and quality of training for the current and future health care workforce.…”
mentioning
confidence: 99%